Literatur Review RCTs: Pengaruh probiotik terhadap sistem kekebalan tubuh pada pasien penyakit infeksi saluran pernapasan - Dhiya Agis Ghazalah; A'immatul Fauziyah (Poltekkes Kemenkes Aceh, 2024)
Background: Probiotics are bacteria that can be immunomodulators and interact with the body's immune system. There is a lack of information regarding the relationship between probiotics and the immune system in individuals who experience illness, especially respiratory infections.Objectives: This article complements the current information contained in several journals about the relationship between probiotics and the immune system in patients with respiratory tract infections.Methods: This descriptive study used a systematic literature review method and was conducted from February to May 2024. Literature from publication years 2014–2024 was obtained from PubMed, Google Scholar, Research Gate, and ScienceDirect. Data collection and analysis used the Preferred Reporting Items for Systematic Reviews (PRISMA) guidelines. A total of 71 articles were collected and selected in stages based on predetermined inclusion criteria. Four articles were successfully selected and then analyzed to find similarities, differences, and perspectives. The data was presented in the form of an extraction table for the population of all age ranges who experienced respiratory infectious diseases. The samples taken were those experiencing respiratory infectious diseases and taking probiotics.Results: Probiotics affect the immune system in patients with respiratory infections by increasing the size and number of plasma cells that produce immunoglobulin-A (IgA) and T cells..Conclusion: Probiotics affect the immune system of infectious disease patients by modulating the innate immune system as well as their antiviral properties. This is in line with previous research information where probiotics are effective in reducing the effects of respiratory infections and improving the immune system.KeywordsRespiratory Infectious Diseases, Probiotics, and the Immune System